Analysis of Essential Oil in Jerusalem Artichoke (Helianthus tuberosus L.) Leaves and Tubers by Gas Chromatography-Mass Spectrometry - Zead Helmi; Khaldun Mohammad Al Azzam; Yuliya Tsymbalista; Refat Abo Ghazleh; Hassan Shaibah; Hassan Aboul-Enein (Tabriz University of Medical Sciences, 2014)
Purpose: To investigate, for the first time, the chemical composition of essential oil of the tubers and leaves of Jerusalem artichoke (Helianthus tuberosus L.), a species of sunflower native to eastern North America, growing in Ukraine. Methods: A hydrodistillation apparatus was used for the extraction of volatile components and then it was analysed by gas chromatography equipped with a split-splitless injector (split ratio, 1:50) and flame ionization detector (FID). The oil was analyzed under linear temperature programming applied at 4°C/min from 50°C - 340°C. Temperatures of the injector and FID detector were maintained at 280°C and 300°C, respectively. The chemical analysis of the oil was carried out using gas chromatography coupled to mass spectrometry (GC-MS), to determine the chemical composition of the volatile fraction. Results: The essential oils content ranged from 0.00019 to 0.03486 and 0.00011 to 0.00205 (g/100g), in leaves and tubers, respectively. The qualitative and quantitative analysis led to the identification of 17 components in both species samples. The major component found in leaves and tubers was (-)-β-bisabolene with 70.7% and 63.1%, respectively. Conclusion:> Essential oil profile of Jerusalem artichoke species showed significant differences between leaves and tubers species. Additionally, the leaves of Jerusalem artichoke are a promising source of natural β-bisabolene.